Open literacy and the problem of access refusal - Hall, Robyn (My University, 2012)
The swift evolution of Open Access (OA) publishing of scholarly works has been driven by researchers and librarians who recognize the societal benefits of these resources being freely available on the Internet. Especially in fields relevant to Science, Technology and Medicine, high quality OA content can benefit people conducting both personal and professional research anywhere in the world. These resources can prove exceptionally valuable to students whose access to scholarly research materials may be limited by costly journal subscriptions both while they are in school and long after they have graduated. This presentation will draw on findings from an exploratory research study that involved a survey sent to academic librarians across Canada questioning the degree to which they are educating students about Open Access research materials and their motivations for and against doing so. Based on participants’ responses, suggested teaching strategies and promotional initiatives will be shared with session attendees. Information literacy teaching methods discussed aim to foster a broader understanding of Open resources and overall scholarly publishing processes among students developing critical and sustainable researching skills.
Presented on May 23, 2012 at the Workshop for Instruction in Library Use (WILU) conference held at MacEwan University in Edmonton, Alberta.
Keywords: open access; open literacy; undergraduate education